IMPORTANCE OF STRESS AND INTONATION IN PHONETICS - Rasulova Shahnoza Abduvasi qizi (Ecominds Press, 2026)
This article explores the significance of stress and intonation as key prosodic features in phonetics. The study examines how stress and intonation contribute to the clarity, naturalness, and effectiveness of spoken English. Particular attention is given to the role of stress in highlighting important information and distinguishing meaning at the word and sentence levels. In addition, the article analyzes intonation patterns and their communicative functions, including the expression of attitudes, emotions, and speaker intentions. The findings suggest that accurate use of stress and intonation is essential for successful communication and intelligible pronunciation. The study also emphasizes the importance of teaching stress and intonation in the process of English language learning.
Keywords: Phonetics, linguistics, speech sounds, articulatory phonetics, acoustic phonetics, auditory phonetics, phonology, stress, intonation, spoken communication.